Alchemical Infrasturctures: Making Blockchain in Iceland - Kyle Cassidy; Katie Gressitt-Diaz; Zane Griffin Talley Cooper; Etienne Jacquot (2020)
Alchemical Infrastructures: Making Blockchain in Iceland” explores not simply the mining of cryptocurrency, but the complicated political, and energy-intensive practice of making cryptocurrency in Iceland; a combinatory process of infrastructures, social systems, political institutions, and desires, all intentionally brought together in search of new monetary futures — or in other words, alchemy. The project assembles and mixes three different modes of qualitative research in an attempt to synthesize an understanding of what the practice of blockchain looks, feels, smells, and sounds like. This multi-modal triad includes an experimental documentary film, produced in 360-degree immersive video, materializing and spatializing the practice of blockchain in Iceland by blending multiple voices and environments. Conceptual sound work by Katie Gressitt-Diaz explores the variated sonic environments conjured forth in the alchemical making of cryptocurrency. Lastly, Cassidy's photo series highlights the personal stakes, ambitions, and passions of individuals involved in Iceland’s cryptocurrency ecology.